1985
DOI: 10.1159/000183523
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Methylguanidine in Isolated Rat Hepatocytes and in vivo

Abstract: To clarify the organ in which methylguanidine is synthesized, high doses of creatinine, which is known to stimulate the synthesis of methylguanidine, were administered to male Wistar rats intraperitoneally. Various tissues of the rats were frozen by a freeze clamp method before and 1, 2 and 3 h after injection, and methylguanidine was determined by high-pressure liquid chromatography using 9,10-phenanthrenequinone for fluorometric determination. We found evidence that the liver, kidney, lung, muscle, red blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 11 publications
1
40
0
Order By: Relevance
“…Based on the reported Crn levels in rat organs (Figure 4) (7), and the reported MG levels in rat organs induced by Crn injection (21,24) and autoradiogram 14 C-Crn (20), sites and organs where Crn scavenges •OH in mammals was presumed ( Figure 5). One-way flow of Crn from muscles and the brain, where Crn is synthesized and its concentration remains at a high level, into blood vessels was observed.…”
Section: Prediction Of Sites Where Crn Scavenges •Oh In Mammalsmentioning
confidence: 99%
“…Based on the reported Crn levels in rat organs (Figure 4) (7), and the reported MG levels in rat organs induced by Crn injection (21,24) and autoradiogram 14 C-Crn (20), sites and organs where Crn scavenges •OH in mammals was presumed ( Figure 5). One-way flow of Crn from muscles and the brain, where Crn is synthesized and its concentration remains at a high level, into blood vessels was observed.…”
Section: Prediction Of Sites Where Crn Scavenges •Oh In Mammalsmentioning
confidence: 99%
“…[1][2][3] Studies revealed that the liver and the kidneys oxidize CTN into creatol, which is converted into MG. [4][5][6][7] Oxidation of CTN with active oxygen (e.g., hydrogen peroxide) was proven to generate MG, whereas scavengers of active oxygen (e.g., glutathione, sorbitol) considerably reduced MG synthesis. 8 MG is expelled mainly from the kidney and is considered as not only a neurotoxin [9][10][11] but also a critical uremic toxin.…”
Section: Introductionmentioning
confidence: 99%
“…It is also conceivable that for unknown physiological reasons the rabbit or rabbit kidney needs high tissular levels of GAA, CT and CTN. The production of MG from CTN has been demonstrated in rat hepatocytes (Nagase, Aoyagi, Narita & Tojo, 1985;Nagase, Aoyagi, Sakamoto, Ishikawa & Narita, 1992). Since the plasma (< 0-020 tM; n = 11 rabbits) and renal concentrations of MG were very low in rabbit compared with rat (Levillain et al 1995), we hypothesized that the intensity of this metabolic pathway might be weaker in the rabbit.…”
Section: Discussionmentioning
confidence: 98%